Improving employee motivation at the Card Services Business Department of Vietcombank’s Ngo Quyen Transaction Centre - Nguyen, Le Duc (Khoa Quốc tế, ĐHQGHN, 2020)
The thesis concludes with the recommendations to improve employee motivation at the Center. These recommendations are really necessary for the Card Services Business Department if they want to possess a strong pool of employees. The recommendations are also practical and applicable to the situation of the company.